Consumer Complaint Application Design at PT. Tritunggal Makmur Indonesia - Muhammad Rizal; Sharyanto; Bernadus Gunawan Sudarsono (Journal of Engineering, Technology and Computing (JETCom), 2022)
PT. Tritunggal Makmur Indonesia (Fujishopid) is a retail or retail company that concentrates or focuses on a category of electronic products such as cameras or other camera devices. Of course PT. Tritunggal Makmur Indonesia prioritizes customer trust and satisfaction, to provide customer needs. At this time PT. Tritunggal Makmur Indonesia only uses customer complaints services in the form of notification reports via short messages or by telephone. The purpose of this research is to design an information system for the design and manufacture of a consumer complaint information system. The methods used are interview methods, observation methods and literature study methods. Design and manufacture of consumer complaints information system at PT. Web-based Tritunggal Makmur Indonesia uses a system modeling with the Unified Modeling Language (UML) method using the Personal Home Page (PHP) programming language and My Structured Query Language (MySQL) as the database. The consumer complaint information system can be one solution to increase consumer confidence, and simplify the complaint or complaint process to make it easier, faster and timely. And also can help increase profits at PT. The Prosperous Trinity of Indonesia.